Odpowiedź :
1)
[tex](a+b)(c+d) = ac + ad + bc + bd[/tex]
[tex](3a+2b)(a-b) = 3a^{2}-3ab + 2ab -2b^{2} = 3a^{2}-ab - 2b^{2}\\\\(3m-2)(2m-1) = 6m^{2}-3m-4m+1 = 6m^{2}-7m+1\\\\(a-3c)(8a+5c) = 8a^{2}+5ac -24ac-15c^{2} = 8a^{2}-16ac-15c^{2}\\\\(2x+3y)(2x-5y) = 4x^{2}-10xy + 6xy - 15y^{2} = 4x^{2}-4xy-15y^{2}\\\\(5x-4y)(3x-2y) = 15x^{2}-10xy - 12xy + 8y^{2} = 15x^{2}-22xy + 8y^{2}[/tex]
2.
[tex]8xy - 16y^{2} = 8y(x - 2y)\\\\5xy - 15x = 5x(y - 3)\\\\25m + 20mn = 5m(5+4n)\\\\20ab^{2}+10a^{3}b^{3}-25ab = 5ab(4b+2a^{2}b^{2}-5)[/tex]